Regulation of plant cell wall degradation by light in Trichoderma - Monika Schmoll (Fungal Biology and Biotechnology, 2018)
Abstract Trichoderma reesei (syn. Hypocrea jecorina) is the model organism for industrial production of plant cell wall degradating enzymes. The integration of light and nutrient signals for adaptation of enzyme production in T. reesei emerged as an important regulatory mechanism to be tackled for strain improvement. Gene regulation specific for cellulase inducing conditions is different in light and darkness with substantial regulation by photoreceptors. Genes regulated by light are clustered in the genome, with several of the clusters overlapping with CAZyme clusters. Major cellulase transcription factor genes and at least 75% of glycoside hydrolase encoding genes show the potential of light dependent regulation. Accordingly, light dependent protein complex formation occurs within the promoters of cellulases and their regulators. Additionally growth on diverse carbon sources is different between light and darkness and dependent on the presence of photoreceptors in several cases. Thereby, also light intensity plays a regulatory role, with cellulase levels dropping at higher light intensities dependent in the strain background. The heterotrimeric G-protein pathway is the most important nutrient signaling pathway in the connection with light response and triggers posttranscriptional regulation of cellulase expression. All G-protein alpha subunits impact cellulase regulation in a light dependent manner. The downstream cAMP pathway is involved in light dependent regulation as well. Connections between the regulatory pathways are mainly established via the photoreceptor ENV1. The effect of photoreceptors on plant cell wall degradation also occurs in the model filamentous fungus Neurospora crassa. In the currently proposed model, T. reesei senses the presence of plant biomass in its environment by detection of building blocks of cellulose and hemicellulose. Interpretation of the respective signals is subsequently adjusted to the requirements in light and darkness (or on the surface versus within the substrate) by an interconnection of nutrient signaling with light response. This review provides an overview on the importance of light, photoreceptors and related signaling pathways for formation of plant cell wall degrading enzymes in T. reesei. Additionally, the relevance of light dependent gene regulation for industrial fermentations with Trichoderma as well as strategies for exploitation of the observed effects are discussed.